Research Reactivity and Distress Protocols for Youth Trauma-related Research: A Scoping Review - Wei, Angela; Khalid, Marria; Ge, Erik; Kang, Jiyeon; Looking Horse, Makaśa; Wekerle, Christine (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2022)
Objective: To explore literature regarding youth with Adverse childhood experiences (ACEs), their potential reactivity to research, and research trauma mitigation protocols.